Why Writing in ESL is difficult For Undergraduates in A Public University in Malaysia - Yah Awg Nik; Azizah Hamzah; Hasif Rafidee Hasbollah (2010)
Writing well and effectively helps our students achieve three important objectives. Firstly, it reinforces the grammatical structures, idioms, and vocabulary. Secondly, writing provides opportunities for our students to be more adventurous with the language, to go beyond what they have learnt and to take risks with the effects of writing. And, finally, the importance of writing lies in the ability to develop language skills in terms of fluency, accuracy and appropriateness, in the communication of meanings and messages. This paper attempts to investigate a comparative study on the first-degree students' writing performance and the problems that hinder students' perception of good writing skills. As English Language is used in all the subjects taught in their degree performance, these students should acquire and also achieve some kind of satisfactory level of writing proficiency. Lecturers expect them to use and write daily tasks, assignments and answer examination questions using English proficiently and effectively. In this study, we found that the students from the Diploma Programme acquired better writing skills than the Matriculation students. The Diploma students performed better in all the five writing components like content, vocabulary, organization, language use and mechanics. This was because the Diploma students had more exposure in English as all the subjects were taught in English Language. Therefore, the Matriculation students were slightly less proficient in their writing performance compared with the Diploma students. The most significant component in writing that hindered their writing proficiency was language use. Both the Diploma and Matriculation students scored very low percentage in this component. We recommend writing lecturers to provide our students ample time and opportunities for them to write and form ideas clearly. Choosing topics for students to write with care nurture the development of their composing abilities, and we should focus - - on helping students to become aware of how and why they write, and encouraging them to write freely, fluently and well.